Optimization of CO2 methanation process using Ni-Fe/Al2O3 catalyst at low temperatures - Yurika Dewi Safitri Liza; Fadarina H C; Anerasari Mediniariasty; Robert Junaidi (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
Carbon dioxide is one of the major contributors to the greenhouse effect. According to IEA data, energy-related carbon dioxide emissions increased by 6 % in 2021 to 36.3 billion tonnes. Methanation of carbon dioxide, known as the Sabatier reaction, is an exothermic reaction in which hydrogen and carbon dioxide react to form methane and water as a by-product. Methane is a colorless, odorless, non-toxic but flammable and hazardous gas. Nickel, Rhodium, and Ruthenium catalysts are some of the most widely used active catalytic constituents in CO2 methanation. Al2O3, SiO2, CeO2, ZrO2, TiO2, Nb2O5, and combinations of other constituents have been widely proposed and studied as catalyst supports. In this study, a Nickel catalyst was used with a combination of Al2O3 as a support and Fe as a promoter. The Nickel catalyst was chosen because it can absorb hydrogen, is cheap, and is very selective in methane formation. This study was conducted in situ, by reacting 1 gr, 2 gr, and 3 gr of Ni catalyst powder; 1 gr, 2 gr, and 3 gr of Al powder; Fe powder as much as 1 gr and 2 gr with 1 M NaOH solution which is heated while stirring at a speed of 100 rpm for 60 minutes. The highest methane gas yield was obtained in sample 10 with a mass of Ni, Al, and Fe respectively 3 gr, 1 gr, and 2 gr of 10.07 % with a CO2 conversion of 2.70 %. The more Ni and Fe catalyst